Freedom fighter: Casimir Pulaski - Abodaher, David J. (New York, J. Messner, 1969)
A biography of the exiled Polish leader who joined the forces of George Washington to fight the British.
Bibliography: p. 183.
Keywords: Pułaski, Kazimierz, -- 1747-1779 -- Juvenile literature; Pulaski, Casimir, -- 1747-1779.; United States -- History -- Revolution, 1775-1783 -- Biography